"Trigger Warnings": Balancing challenging material with overwhelming students - Susan Gere (Academic Chairpersons Conference Proceedings, 2015)
Students with trauma histories are requesting explicit alerts called "trigger warnings" that required course material may be upsetting to them. This workshop provides a conceptual discussion of what constitutes student trauma history; a summary of a qualitative research project with faculty who teach student trauma survivors; and practical suggestions for balancing healthy classroom culture with the demands of content. Relevant for all chairpersons.
Keywords: trigger warnings; social microcosm; student trauma history; classroom climate; innovative strategies